2005
DOI: 10.1007/s11069-004-4549-4
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Application of a Flood Risk Model for the Czech Republic

Abstract: A flood risk model was developed for the Czech Republic to calculate the probability of insured losses from flood events. The model was GIS based, making use of a 100 m horizontal resolution DTM and a network of the major rivers in the country. A review of historical flooding was undertaken to define the worst and most widespread flood events. Synthetic flood events were generated based on a study of the spatial variation in magnitude of river flows from selected historical flood events going back to 1935. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 1 publication
0
50
0
Order By: Relevance
“…Several features in the flood generation of large events are in common to most types of floods and allow the definition of a general time window for flood peak detection. For example, Rodda (2005) uses a 10 day envelope around the date when the peak discharge of a historical flood event was recorded. This time window is then interrogated to find the maximum mean daily discharge for each station for each event.…”
Section: Temporal Envelope Wmentioning
confidence: 99%
See 2 more Smart Citations
“…Several features in the flood generation of large events are in common to most types of floods and allow the definition of a general time window for flood peak detection. For example, Rodda (2005) uses a 10 day envelope around the date when the peak discharge of a historical flood event was recorded. This time window is then interrogated to find the maximum mean daily discharge for each station for each event.…”
Section: Temporal Envelope Wmentioning
confidence: 99%
“…Rodda (2005) demonstrated that past floods can be employed to derive synthetic trans-basin flood scenarios for the main rivers in the Czech Republic. He assembled a set consisting of the 11 most severe historical floods from 1935 to 2002 using reports and local knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Rodda (2005) used maximum discharges to express flood extremity in the Czech Republic. He considered the ratio of the maximum mean daily discharge to the median annual flood.…”
Section: Introductionmentioning
confidence: 99%
“…Several flood identification methods taking the spatio-temporal coherence of flooding into account have recently been proposed by e.g. Rodda (2005), Merz and Blöschl (2003), Keef et al (2009), Uhlemann et al (2010) and Ghizzoni et al (2012). We identified large-scale flood events in the Elbe River basin using an approach proposed by Uhlemann et al (2010) as the method is non-restrictive to a certain return period and takes the simultaneous or time shifted occurrence of peak discharges at many sites into account.…”
Section: Flood Event Identificationmentioning
confidence: 99%